Maternal choline supplementation modulates cognition and induces anti-inflammatory signaling in the prefrontal cortex of adolescent rats exposed to maternal immune activation - King, Cole J. (Kansas State University, 2024)
Maternal infection has long been described as a risk factor for neurodevelopmental disorders, especially autism spectrum disorders (ASD) and schizophrenia. Although many pathogens do not cross the placenta and infect the developing fetus directly, the maternal immune response to them is sufficient to alter fetal neurodevelopment, a phenomenon termed maternal immune activation (MIA). Low maternal choline is also a risk factor for neurodevelopmental disorders, and most pregnant people do not receive enough of it. In addition to its role in neurodevelopment, choline is capable of inducing anti-inflammatory signaling through a nicotinic pathway. Therefore, it was hypothesized that maternal choline supplementation would blunt the neurodevelopmental impact of MIA in offspring through long- term instigation of cholinergic anti-inflammatory signaling. To model MIA in rats, the viral mimetic polyinosinic:polycytidylic acid (poly(I:C)) was used to elicit a maternal antiviral innate immune response in dams both with and without choline supplementation. Offspring were reared to both early and late adolescent stages (postnatal days 28 and 50, respectively), where cognition and anxiety-related behaviors were examined. After behavioral testing, animals were euthanized, and their prefrontal cortices (PFCs) were collected for analysis. MIA offspring demonstrated sex-specific patterns of altered cognition and repetitive behaviors, which were modulated by maternal choline supplementation. Choline supplementation also bolstered anti-inflammatory signaling in the PFCs of MIA animals at both early and late adolescent stages. These findings suggest that maternal choline supplementation may be sufficient to blunt some of the behavioral and neurobiological impacts of inflammatory exposures in utero, indicating that it may be a cheap, safe, and effective intervention for neurodevelopmental disorders.
Keywords: Maternal immune activation; Neurodevelopmental disorders; Choline; Prefrontal cortex; Behavior; Cognition